The recurrence of colonic volvulus due to nonrotation after intestinal resection in adulthood: a case report - Yusuke Sakimura; Hirotaka Kitamura; Noriyuki Inaki; Hiroyuki Bando (Surgical Case Reports, 2019)
Abstract Background Intestinal nonrotation is a rare congenital condition that causes fatal colonic volvulus at any age. Once volvulus attack occurs, radical surgical therapy is required for treatment and the prevention of recurrence. This report describes the case of an adult female patient with a recurrence of cecum volvulus due to intestinal nonrotation after transverse colon resection for colonic volvulus. Case presentation A 27-year-old female visited our emergency room (ER) with intermittent abdominal pain and nausea. Enhanced computed tomography (CT) showed enlargement of the level of the ascending and transverse colon and an obstruction with a whirlpool sign at the transverse colon. The small intestine was distributed on the right side of the abdominal cavity, and the large intestine occupied the left side. She was diagnosed with volvulus with intestinal nonrotation, and emergency surgery was performed. Surgical examination indicated that the ascending colon to the transverse colon was not fixed to the retroperitoneum, and the transverse colon was rotated 180° clockwise. The axis of the volvulus was a mesenteric adhesion of the transverse colon. The involved transverse colon was resected, and the intestine was reconstructed by functional end-to-end anastomosis (FEEA). Six years after the initial surgery, the patient presented to the ER with abdominal fullness and lower abdominal pain. Enhanced CT revealed that the cecum, ascending colon, and remaining transverse colon were dilated with an obstruction. The appendix was located in the left upper abdominal cavity. The clinical diagnosis was cecal volvulus with intestinal nonrotation. An emergency laparotomy revealed that the cecum was rotated 180° clockwise. The terminal ileum to the remaining transverse colon was resected, and FEEA was performed. Seven months later, she suffered obstruction of the intestine caused by an operative adhesion, and conservative treatment was successful. The patient has had no abdominal symptoms for one and a half years so far. Conclusions Surgeons should realize that nonrotation of the intestines induces volvulus in adulthood and should familiarize themselves with its clinical findings, appropriate treatment, and prognosis. Even after surgical treatment, awareness of the recurrence of volvulus should be maintained to avoid a late diagnosis.